Challenges and Opportunities of Assessing Efficiency of Digital Technology Introduction in Construction Projects - T. V. Vashchenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
Today for all countries of the world digitalization became not only possible but also a necessary tool of providing planned innovation growth in economy, a rise in production efficiency, competitiveness of products and services, increase in quality and standard of living of the population. At the same time due to numerous causes arising from specificity of organization of production process its transformation in the digital format often becomes a complicated task for many sectors of economy and fields of activities that requires specific tools and approaches for implementation. Construction industry is a conservative one, the problem of its digitalization needs serious attention, including the governmental level. The article analyzes key factors hindering digitalization introduction in construction industry and making assessment of its efficiency more difficult; it studied both negative and positive aspects affecting decisions made by management of construction companies. The authors propose optimum indicators of assessment in view of investors interested both in increasing their capitals and in development of construction field and describe possible algorithms and methods of estimating investment-construction projects, where new technologies could be used.